2012
DOI: 10.1515/rjti-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Asphalt Mixtures with Limestone Aggregate for Base Layer

Abstract: Asphalt mixtures are mixtures of mineral aggregates, filler, bitumen and eventually additives in proportions determined by recipe designed in the laboratory. Asphalt mixtures used as base course are bituminous concrete. The natural aggregates are granular materials of mineral origin that come from natural or artificial crushing of the rocks. In our country there are the various rocks: eruptive or magmatic rocks, metamorphic rocks, sedimentary rocks. To the category of sedimentary rocks belong limesto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Metamorphic rocks are also considered with extremely high densities and mechanical strengths. Meanwhile, sedimentary rocks are characterized by a relatively large porosity and a distinct stratification, which results in low mechanical resistance which varies with the direction of force [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metamorphic rocks are also considered with extremely high densities and mechanical strengths. Meanwhile, sedimentary rocks are characterized by a relatively large porosity and a distinct stratification, which results in low mechanical resistance which varies with the direction of force [1].…”
Section: Introductionmentioning
confidence: 99%
“…Malaysia also produces IOP Publishing doi:10.1088/1755-1315/1135/1/012054 2 vast and diverse quantities of aggregates, the majority of which consist of granite and limestone and the remainder of which are basalt, diorite, and gravel [2]. Limestone is employed less frequently in heavy traffic paving structures as a result of the concentration of large companies and aggregate factories on granite as the primary ingredient [1]. In recent years, however, the idea of using limestone in road applications has gained traction, as testing samples of varying limestone quality revealed that highquality limestone may outperform granite in terms of mechanical properties.…”
Section: Introductionmentioning
confidence: 99%